Studies on the Antioxidant Content and Antimicrobial Activity of Cucumber (Cucumis sativus) Peels Collected from Bagmari, Kolkata, West Bengal, India - Debasree Ghosh; Hamidur Rahaman Mondal (Emerging Trends in Metabolites, 2025)
Cucumber (Cucumis sativus) is widely consumed across the globe, yet its peels are commonly discarded as waste, despite possessing a wealth of bioactive compounds. Recent studies have highlighted that these peels contain substantial amounts of antioxidants, antibacterial, anti-inflammatory, and anticarcinogenic properties, making them a promising candidate for value-added applications. In this study, methanolic extracts (80% v/v) of cucumber peels were systematically analyzed to assess their total phenolic content (TPC), total flavonoid content (TFC), and ascorbic acid concentration. The analyses were carried out using well-established protocols, including the Folin–Ciocalteu method for TPC, the Aluminum Chloride colorimetric method for TFC, and spectrophotometric analysis for ascorbic acid quantification. The results demonstrated that the peel extracts are rich in phenolic compounds and flavonoids, along with a notable amount of ascorbic acid, indicating strong antioxidant potential. Furthermore, the extracts exhibited significant antibacterial activity against selected microbial strains, underscoring their potential as natural antibacterial agents. These findings suggest that cucumber peels, often overlooked and discarded, could serve as a sustainable source of natural preservatives in the food industry. Moreover, the use of such agro-waste not only promotes environmental sustainability by reducing organic waste but also adds economic value through the development of functional food ingredients or nutraceuticals. Further research is warranted to optimize extraction techniques, explore in-depth biological activities, and evaluate the practical applications of cucumber peel extracts in real food systems and pharmaceutical formulations.
Keywords: Keywords: Cucumber peel; Phytochemicals; antimicrobial activity; vitamin C